1.2+x=.6(4+x)

Simple and best practice solution for 1.2+x=.6(4+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.2+x=.6(4+x) equation:


Simplifying
1.2 + x = 0.6(4 + x)
1.2 + x = (4 * 0.6 + x * 0.6)
1.2 + x = (2.4 + 0.6x)

Solving
1.2 + x = 2.4 + 0.6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.6x' to each side of the equation.
1.2 + x + -0.6x = 2.4 + 0.6x + -0.6x

Combine like terms: x + -0.6x = 0.4x
1.2 + 0.4x = 2.4 + 0.6x + -0.6x

Combine like terms: 0.6x + -0.6x = 0.0
1.2 + 0.4x = 2.4 + 0.0
1.2 + 0.4x = 2.4

Add '-1.2' to each side of the equation.
1.2 + -1.2 + 0.4x = 2.4 + -1.2

Combine like terms: 1.2 + -1.2 = 0.0
0.0 + 0.4x = 2.4 + -1.2
0.4x = 2.4 + -1.2

Combine like terms: 2.4 + -1.2 = 1.2
0.4x = 1.2

Divide each side by '0.4'.
x = 3

Simplifying
x = 3

See similar equations:

| 2x+5-x=x+8 | | x^2+4mx+4=0 | | -3(-7+4v)-6=35-2v | | 18x^4-(8x^2)=2 | | x-4+2x*2=2x+4 | | 7+.30x=.20(7+x) | | 0=x^4-9y^2 | | (18x^4)-(8x^2)=2 | | (18x^4)-8x^2=2 | | 6(4x-1)2+5=-17(4x-1) | | C/d=3.14 | | 4a-ab= | | x/8-x/7=2 | | 7+1x=.20(7+x) | | 2-4/7 | | -4x^2-3x+5=0 | | 2*(x+4)-3*x=8 | | 12+.60x=.40(60+x) | | 6(2-8n)=5y-36 | | R7/R12 | | (2-4/7)/ | | y=-3(-3)-1 | | 1=-r-4 | | m/15-7=-8 | | -2(8+3n)=-28-8n | | 18+.60x=.40(60+x) | | 4t^3+3t^2= | | x^2-690x=1248 | | -(-2x+2)=7y+-14 | | 12v+8v= | | -6(10+n)=-156 | | t^3+t^2+t= |

Equations solver categories